INOVASI PENGERING IKAN MENGGUNAKAN HOME DRIED SYSTEM UNTUK MENINGKATKAN PRODUKSI IKAN PAKANG DESA KUALA GEULUMPANG KECAMATAN JULOK KABUPATEN ACEH TIMUR - Puji Wahyuningsih; wan Alamsyah; Rachmad Almi Putra; T. Andi Fadlly (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
Kuala Geulumpang village is one of the villages in Julok subdistrict where most of the community is a business group that processes fish into cracker or known as pakang fish. One of the problems experienced by the business group is the drying process, especially in the rainy season which result decrease in the color quality and taste of pakang fish products. This service program aims to provide a solution for drying media that is not depend by weather conditions, namely a home dried system using an integrated solar panel media based on solar energy through solar cell and current batteries storage. This method has advantages compared with conventional methods are that are not affected by the weather, faster the drying process, minimizes fish damage caused by decaying so that the quality of the product is maintained and can be accepted by consumers on time. Through the application of fish dryer technology is expected to increase the production and quality of pakang fish produced by the community of Kuala Geulumpang Village so that it can improve the community's economy.